Earth-size planet formation in the habitable zone of circumbinary stars - Barbosa, G. O. [UNESP]; Winter, O. C. [UNESP]; Amarante, A. [UNESP]; Izidoro, A. [UNESP]; Domingos, R. C. [UNESP]; Macau, E. E.N. (Oxford University Press (OUP), 2020)
This work investigates the possibility of close binary (CB) star systems having Earth-size planets within their habitable zones (HZs). First, we selected all known CB systems with confirmed planets (totaling 22 systems) to calculate the boundaries of their respective HZs. However, only eight systems had all the data necessary for the computation of HZ. Then, we numerically explored the stability within HZs for each one of the eight systems using test particles. From the results, we selected five systems that have stable regions inside HZs, namely Kepler-34, 35, 38, 413, and 453. For these five cases of systems with stable regions in HZ, we perform a series of numerical simulations for planet formation considering discs composed of planetary embryos and planetesimals, with two distinct density profiles, in addition to the stars and host planets of each system. We found that in the case of the Kepler-34 and 453 systems, no Earth-size planet is formed within HZs. Although planets with Earth-like masses were formed in Kepler-453, they were outside HZ. In contrast, for the Kepler-35 and 38 systems, the results showed that potentially habitable planets are formed in all simulations. In the case of the Kepler-413 system, in just one simulation, a terrestrial planet was formed within HZ.
Keywords: Binaries: close; Planets and satellites: formation